Emerging and accumulating safety signals for the use of estrogen among transgender women - Lauren Schwartz; M. Lal; J. Cohn; Carrie D. Mendoza; Leslie MacMillan (Discover Mental Health)
Abstract Efforts to alleviate the psychological distress of gender dysphoria have included the use of exogenous estrogen (often with anti-androgens) to alter secondary sex characteristics of natal males. In response to the rapid increase in presenting cases among young people, extensive scrutiny has now been brought to bear on these medical interventions for minors, with ESCAP reporting “an urgent need for safeguarding clinical, scientific, and ethical standards.” However, due to the lack of systematic outcome data, the associated risk–benefit profile is unknown. Several recent systematic reviews have found the evidence of benefit to be of low or very low certainty, while some risks, such as infertility, have been long recognized. This paper compiles several emerging and accumulating safety signals in the medical literature. These range from increased rates of previously associated adverse outcomes with long-term estrogen use (e.g., acute cardiovascular events) to associations of estrogen use with newly identified adverse outcomes. Estrogen also induces changes in the brain, raising concerns for negative impacts on mood (e.g., depression) and cognition. These safety signals indicate the need for further investigation and a thorough systematic search for others, which may now be more evident due to the increased number of young people receiving these treatments. There is an urgent need for the evidence base to be improved with more studies, especially those with systematic long-term follow-up and those that can disentangle possible confounders, as well as systematic reviews to help interpret their reliability.